The optical properties of alumina and tirania naofluids / Saktiyaramana Karpayah - Saktiyaramana, Karpayah (2018)
Fossil fuel are known to be the driving force of climate change because they emit substantial amount of greenhouse gases. One way in reducing greenhouse gases into the atmosphere is by changing it into green energy; harnessing and making them much more efficient. Adding nanofluids into base fluids was proven to enhance its physical properties such as thermal conductivity and light absorption. Nanofluids can be used as heat transfer fluid in many heat transfer application. Based on previous studies the most suitable nanofluids that can be used in solar thermal collectors would be carbon based and metal oxide based nanofluids, as both types of materials showed significant enhancement on thermal conductivity with good suspension stability. Therefore in this study the light absorption and transmittance of alumina and titania nanofluids are being investigated. Two step preparation method was used to prepare the sample, with 40 min ultrasonication and PVP as the surfactant. The samples were prepared with volume concentration ranging from 0.02 vol% to 0.1 vol%. The prepared sample were also observed for its stability. The outcome of the results showed that alumina nanofluids was stable for a long period compared to titania nanofluids. Moreover, the samples showed better stability when the pH was maintained at 6.8-7 for titania nanofluid and pH 6.0 to 6.8 for alumina nanofluids. As for the optical properties, distinguishably titania nanofluids showed better light absorption compared to alumina nanofluids. Moreover as for particle loading, light absorbance increases when the nanoparticle concentration increases regardless to the type of nanofluid examined. As For transmittance the result shows that light transmittance for titania nanofluid was lesser. As for nanoparticle concentration to light transmittance, the higher the concentration the lower the transmittance.